50 Gallon Still (Closed) - Dietrich, T. A. (1963)
The still produced water for use in field medical stations.
Keywords: Medical laboratories--Equipment and supplies; Distillation apparatus; Scientific apparatus and instruments; Beckman Instruments, Inc.